The state of family medicine training programmes within the Primary Care and Family Medicine Education network - Klaus B. von Pressentin; Innocent Besigye; Robert Mash; Zelra Malan (AOSIS, 2020)
The 2019 Primary Care and Family Medicine Education network (Primafamed) meeting in Kampala, Uganda, included a workshop that aimed to assess the state of postgraduate family medicine training programmes in the Primafamed network. Forty-six people from 14 African and five other countries were present. The evaluation of programmes or countries according to the stages of change model was compared to a previous assessment made 5 years ago. Most countries have remained at the same stage of change. Two countries appeared to have reversed their readiness to change as Rwanda moved from relapse to pre-contemplation and Mozambique moved from action to contemplation. Malawi, Zambia and Zimbabwe increased their readiness to change and moved from contemplation to action. Countries in the region remain quite diverse in terms of their commitment to family medicine training. Within Primafamed, it is possible for countries with a more advanced stage of change to assist countries with an earlier stage. Primafamed is also supported by a variety of partners outside of Africa. Five years after the previous country-level assessment, family medicine in Africa continues to span across all levels of the stages of change model. Stage-matched interventions aligned with the needs of individual countries should follow. Consequently, this workshop report will serve as a mandate and compass for Primafamed's actions over the next few years, aimed at designing and delivering these interventions. As reiterated in the 2019 Kampala commitment, we should continue developing the discipline of family medicine (the medical 'specialty' of primary care), through alignment of our training programmes to the health needs in the African region.